2018
DOI: 10.3389/fpls.2018.01713
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Plant Chemistry and Multi-Species Interactions in Diversified Agroecosystems

Abstract: Over the past few years, our knowledge of how ecological interactions shape the structure and dynamics of natural communities has rapidly advanced. Plant chemical traits play key roles in these processes because they mediate a diverse range of direct and indirect interactions in a community-wide context. Many chemically mediated interactions have been extensively studied in industrial cropping systems, and thus have focused on simplified, pairwise and linear interactions that rarely incorporate a community per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…Finally, although most research so far has aimed to answer fundamental ecological questions, a few studies have been done in a more applied context, examining phytochemical diversity for crop species, and its potential importance for protection against pest insects (Whitehead and Poveda 2019, Espinosa-García et al 2021, Robinson et al 2022, Bernal et al 2023). Further research on this topic could increase our understanding of how considerations of chemodiversity could be utilized in agroecosystems (Silva et al 2018, Espinosa-García 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although most research so far has aimed to answer fundamental ecological questions, a few studies have been done in a more applied context, examining phytochemical diversity for crop species, and its potential importance for protection against pest insects (Whitehead and Poveda 2019, Espinosa-García et al 2021, Robinson et al 2022, Bernal et al 2023). Further research on this topic could increase our understanding of how considerations of chemodiversity could be utilized in agroecosystems (Silva et al 2018, Espinosa-García 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it could be highly beneficial to manage agroecosystem diversity to increase overall structural PD throughout the agroecosystem, thus reducing damage to crops. It is quite likely that many as yet unknown mechanisms related to PD are involved in the well‐known benefits of agroecosystem diversification for agroecosystem services and sustainable crop production, and we believe this area is a promising one for future research (Hauri et al., In Press; Silva et al., 2018; Vandermeer et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Simpson, inverse Simpson, Shannon–Weiner and higher q values) can be thought of as effective numbers of chromatographic or spectroscopic peaks observed in chemical analysis (Feiner et al., 2018; Hill, 1973; Marion et al., 2015; Richards et al., 2015; Wetzel & Whitehead, 2020). This approach has elucidated the important role of diverse mixtures in shaping trophic interactions in ecological (Dyer et al., 2018) and agricultural (Silva et al., 2018) systems. Recent studies have demonstrated that chemical diversity is an effective measure of synergistic phytochemical mixtures (Gershenzon et al., 2012; Rasmann & Agrawal, 2009; Richards et al., 2016; Whitehead et al., 2013) that affect herbivore performance (Glassmire et al., 2020; Slinn et al., 2018) and can drive community assembly (Glassmire et al., 2016; Harrison et al., 2016; Massad et al., 2017; Poelman et al., 2009; Richards et al., 2015; Salazar et al., 2016a, 2016b; Schuman et al., 2016; Sedio et al., 2017) and contribute to coevolutionary processes (Berenbaum & Zangerl, 1996; Ehrlich & Raven, 1964; Jahner et al., 2017).…”
Section: Introductionmentioning
confidence: 99%